Commentary on Syrian Administrative Court Decision No. 351/2019 - Saeed, Tareeq Shawkt; Shabat, Youssef; Al-Mohammed , Khaled (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This study aims to comment on Syrian Administrative Court Decision No. 351/2019, identifying its strengths and weaknesses regarding the issues raised by the decision and assessing its compatibility with jurisprudential and judicial reasoning. Methods: The study adopted an inductive approach after reviewing several relevant judicial decisions related to the decision under consideration. Results: The study concludes that the inherent jurisdiction to determine the scope of sovereign acts rests with the judiciary. It emphasizes the need to consider these acts as exceptions to the general rule, which entails the judiciary's competence to review all administrative disputes. Additionally, the study finds that administrative discretionary power addresses specific elements in the decision and cannot exist without judicial restrictions or supervision. Furthermore, administrative acts delegated to specialized technical committees and their outcomes play a significant role in making the final decision. Conclusions: The study highlights the necessity of keeping pace with judicial developments in sovereign acts and the freedom of discretion enjoyed by the administration. It recommends implementing clear error review to subject all discretionary actions to judicial scrutiny.